The Effect of Diamond Fraud on Financial Statement Fraud With Beneish M-Score on Manufacturing Companies - Nurfajri, Muhammad; Nugrahanti, Trinandari Prasetyo (West Science Accounting and Finance, 2024)
This study aims to analyze the effect of fraud diamond proxied by pressure, opportunity, rationalization and capability on the effect of fraud that occurs in the company's financial statements with audit committee moderation. The research method was conducted using quantitative research with 240 samples taken in manufacturing in the 2017-2019 period. The type of data used is secondary data. The data analysis used is the Beneish Ratio Index, which is then included in a model, the Beneish M-Score Model using four methods calculated in the Receivables Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI). The results of this study indicate that based on the Beneish M-Score, that financial targets affect financial statement fraud, ineffective monitoring has no effect on financial statements, change in auditor has no effect on financial statement fraud, change in director has no effect on financial statement fraud, the audit committee is able to strengthen the effect of financial targets on financial statement fraud, the audit committee is unable to strengthen the effect of ineffective monitoring on financial statement fraud, the audit committee is able to strengthen the effect of change in auditor on financial statement fraud and the audit committee is unable to strengthen the effect of change in director on financial statement fraud.